Eco-pesantren modeling for environmentally friendly behavior: new lessons from Indonesia - Rihlah Nur Aulia; Hafid Abbas; Nurhattati Nurhattati; Faisal M. Jasin; Mushlihin Mushlihin (International Journal of Evaluation and Research in Education (IJERE), 2024)
Pesantren or Islamic boarding school plays a vital and strategic role in improving environmentally sound education. Eco-pesantren is a movement that puts a high concern for the environment. This study aimed to analyze eco-pesantren modeling techniques in education. It is a case study with a qualitative research method. The research was conducted at Islamic Boarding School Sumber Mental Agama Allah (SPMAA), Turi Lamongan, East Java, Indonesia. Data were collected by observation, interviews, questionnaires, and document studies. This research concluded that modeling techniques can at least be pursued in four main ways: the individual role model of pesantren leaders; infrastructure and their use; governance systems; and culture or traditions. Besides, using integrated modeling techniques at both school and pesantren culture can increase insight and application of environmentally friendly behavior through a direct observation and habituation of healthy educational practices. Modeling can help students turn abstract ideas of green life into actual implementations. Direct observation of continuous practices equips students with the knowledge required to perform expected behaviors. Research on modeling assists eco-pesantren institutions encourage learning and practices about healthy environment. In the global context, it can be a role model for the implementation of environmentally friendly education that promotes environmentally sound learning.